"A" cation polarity control in ACuTe2O7 (A = Sr2+, Ba2+, or Pb2+). - Yeon, J; Kim, S; Hayward, M; Halasyamani, P (2011)
The synthesis and characterization of ACuTe(2)O(7) (A = Sr(2+), Ba(2+), or Pb(2+)) have been carried out. Interestingly, SrCuTe(2)O(7) and PbCuTe(2)O(7) are centrosymmetric and isostructural, whereas BaCuTe(2)O(7) is noncentrosymmetric and polar. All of the materials contain [CuTe(2)O(7)](2-) layers stacked along the b-axis direction that are separated by the "A" cations. The layers are composed of corner-shared CuO(5), TeO(6), and TeO(4) polyhedra. The influence of the "A" cation on the polarity is described by bond valence concepts, including the bond strain index and global instability index. Infrared, UV-vis, thermogravimetric, differential thermal analysis, and magnetic measurements were performed on all three materials. For BaCuTe(2)O(7), second-harmonic generation (SHG), piezoelectric, and polarization measurements were performed. A moderate SHG efficiency of approximately 70 × α-SiO(2) was measured. In addition, we determined that BaCuTe(2)O(7) is not ferroelectric; that is, the macroscopic polarization is not reversible. For BaCuTe(2)O(7), a pyroelectric coefficient of -9.5 μC/m(2)·K at 90 °C and a piezoelectric charge coefficient of 49 pm/V were determined. Crystal data are the following: SrCuTe(2)O(7), orthorhombic, space group Pbcm (No. 57), a = 7.1464(7) Å, b = 15.0609(15) Å, c = 5.4380(5) Å, V = 585.30(10) Å(3), and Z = 4; PbCuTe(2)O(7), orthorhombic, space group Pbcm (No. 57), a = 7.2033(5) Å, b = 15.0468(10) Å, c = 5.4691(4) Å, V = 592.78(7) Å(3), and Z = 4.